Emerging I&C Technologies Under the Shifting Regulatory Environment in South Korea - Heo, Gyunyoung; Seong, Poong Hyun; Kang, Hyun Gook (Frontiers in Energy Research, 2015)
The role of probabilistic safety assessment (PSA) has been supplementary and risk-informed applications based on the insight from PSA have also been utilized limitedly in the licensing process for nuclear power plants (NPPs) in South Korea. However, as the technical significance of PSA is getting increased, PSA has become a mandatory part of Safety Analysis Reports and Periodic Safety Review. It is worthwhile to highlight the role of emerging instrumentation and control (I&C) technologies including human–machine interface (HMI) in developing more credible and realistic PSA models. Particularly, it is expected that the information technology (i.e., software) embedded in digital I&C can adjust over- and under conservatism in analyzing risk. In this study, authors proposed the cases which would be able to significantly reduce risk if advanced I&C supported by information technologies is applied. In regard, the several enabling techniques and their effects are proposed. In order to improve the commercial competitiveness of NPPs, the need of collaboration and synergetic outcome of I&C, HMI, and PSA should be emphasized.